A review on second-life of Li-ion batteries: prospects, challenges, and issues. (15th February 2022) - Shahjalal, Mohammad; Roy, Probir Kumar; Shams, Tamanna; Fly, Ashley; Chowdhury, Jahedul Islam; Ahmed, Md. Rishad; Liu, Kailong
Abstract: High energy density has made Li-ion battery become a reliable energy storage technology for transport-grid applications. Safely disposing batteries that below 80% of their nominal capacity is a matter of great concern to reduce overall carbon footprint. As battery typically accounts for 40% of the total cost of an electrical vehicle, it becomes necessary to combine reutilization and recycling for extending the lifetime of retired automotive batteries and make the overall battery supply chain profitable rather than dumping them directly. From an economic, technical, and environmental standpoint, this paper provides a comprehensive overview of the present state of second-life Li-ion batteries through exploring relevant literature. Specifically, the fundamental of Li-ion battery degradation and experimental approaches are first surveyed. After examining the obstacles and methods of reusing and recycling Li-ion battery, related applications, cost issues, and business models of second-life Li-ion batteries are discussed. By offering a systematical survey of current status of recycled Li-ion battery, this review could inform commercial technology selections and academic research agendas alike, thus boosting progress in Li-ion battery second-life applications. Highlights: Second-life battery is economically benefitting and environmentally sustainable. An elaborate discussion on the identification of battery degradation is presented. Profitable economics of the second-life battery is discussed. Cost analysis and business model for second-life battery application are discussed. Challenges and potential solutions for second-life battery application are identified.